Examining Poetry / Peter Benton. - Benton, Peter; Stratta, Leslie; Southern Regional Examinations Board, Southampton (England). (Washington, D.C. : Distributed by ERIC Clearinghouse, 1986)
Elaborated as a response to a traditional set of secondary school poetry examinations that are called "sterile and outmoded," this report resulted from a series of seminars held in England by literature educators. The report offers extensive guidelines for modernizing the exams, examples of student critical writing about particular poems, and student responses to the educators' modernization plans. Part 1, "Exploring Possible Achievements," assesses the efficacy of current exam guidelines, offering concrete examples using student comments on several poems. Part 2, "Experimenting with Guidelines," discusses strategies for the improvement of the guidelines, such as changing the wording or offering alternate sets of guidelines for different students. Part 3, "Ideological Issues: A Further Experiment," considers a particularly complex question, ideology, and focuses on the most accessible use of the concept--consciously committed poetry, and especially satirical criticism and protest about political and social mores. Part 4, "Questions on Poetry Anthologies," argues against exam questions that generalize about poetic texts and for a less rigid system which would enlist the collaboration of the students and allow for a more independent response. (NKA)
Availability: Southern Regional Examinations Board, Avondale House, 33 Carlton Crescent, Southampton, S09 4YL England, United Kingdom (35 pence).
Practitioners.
Teachers.
Microfiche.
Keywords: Educational Change; Educational Improvement; Educational Innovation; Evaluation Criteria; Evaluation Methods; Feedback; Foreign Countries; Guidelines; Ideology; Literary Criticism; Literary Devices; Literature Appreciation; Modernization; Poetry; Reader Response; Reading Comprehension; Secondary Education; Test Construction; Test Format; Test Interpretation; Test Reliability; Guides, Classroom -- Teacher; Reports, Descriptive; Opinion Papers